Persepsi Generasi Muda Di Nusajaya Terhadap Seni Tarian Zapin Negeri Johor - Hasri, Jemain (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study was conducted to assess the level of interest and not the interest of the younger generation of art Zapin, examine the level of their knowledge, and their perception of Zapin and steps you can take to attract them. Methods Data were collected using a questionnaire respondents and interview officers from the Johor Heritage and dance teacher. This study analyzed qualitatively and selected locations are Nusajaya Johor. Overall results of the analysis of the study shows that they recognize the art of dance Zapin but not in depth but also the knowledge that there is not a guarantee for those interested in the art of the dance.